2009
DOI: 10.1161/circresaha.108.190918
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP-Activated Protein Kinase by Metformin Improves Left Ventricular Function and Survival in Heart Failure

Abstract: Abstract-Clinical studies have reported that the widely used antihyperglycemic drug metformin significantly reduces cardiac risk factors and improves clinical outcomes in patients with heart failure. The mechanisms by which metformin exerts these cardioprotective effects remain unclear and may be independent of antihyperglycemic effects. We tested the hypothesis that chronic activation of AMP-activated protein kinase (AMPK) with low-dose metformin exerts beneficial effects on cardiac function and survival in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
330
4
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(353 citation statements)
references
References 41 publications
15
330
4
4
Order By: Relevance
“…Our observation is consolidated by a recent study which has also shown that Ca 2ϩ -dependent AMPK activation is required for p65/RelA binding to nuclear DNA in thrombin-stimulated endothelial cells, which is mediated by protein kinase C␦ and p38 MAPK (53). In support of our conclusion, other investigators have noted that AMPK can attenuate apoptotic signaling in biological systems other than the endothelium, such as cardiomyocytes (54,55). Capano and Crompton (56) were one of the first investigators to bridge the gaps between AMPK signaling, p38 MAPK, and apoptotic cell death in ischemic hearts.…”
Section: Discussionsupporting
confidence: 88%
“…Our observation is consolidated by a recent study which has also shown that Ca 2ϩ -dependent AMPK activation is required for p65/RelA binding to nuclear DNA in thrombin-stimulated endothelial cells, which is mediated by protein kinase C␦ and p38 MAPK (53). In support of our conclusion, other investigators have noted that AMPK can attenuate apoptotic signaling in biological systems other than the endothelium, such as cardiomyocytes (54,55). Capano and Crompton (56) were one of the first investigators to bridge the gaps between AMPK signaling, p38 MAPK, and apoptotic cell death in ischemic hearts.…”
Section: Discussionsupporting
confidence: 88%
“…Transient AMPK activation can have pro-survival effects in neurons which are partially mediated by increased GLUT 3 translocation to the cell membrane and increased glucose uptake and utilization (Weisova et al 2009, Culmsee et al 2001, Gundewar et al 2009). On the contrary, increased AMPK activation has been associated with excitotoxicity, stroke-induced injury in vivo, and neurodegeneration in Huntington's disease (McCullough et al 2005, Concannon et al 2010, Mochel et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Dans un modèle d'insuffisance cardiaque chez le rongeur, la metformine favorise l'adaptation métabolique du coeur en stimulant l'utilisation progressive du glucose à la place des acides gras. Cette action serait dépendante d'une activation de l'AMPK qui participe à la stimulation de la capture du glucose et du flux glycolytique face à la privation d'oxygène [25]. L'utilisation de la metformine chez les patients diabé-tiques ayant des antécédents d'insuffisance cardiaque a montré des effets bénéfiques avec une réduction de la mortalité et de la morbidité [26].…”
Section: Effet Cardioprotecteur : La Botte Secrète De La Metformineunclassified